PENGARUH MODEL PEMBELAJARAN MASTERY LEARNING TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATAPELAJARAN IPAS DI SD HARAPAN BARU MEDAN - Arisan Laia; Juliana; Reflina Sinaga; Eka Kartika Silalahi; Paska Sriulina Tarigan; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Mastery Learning model on student learning outcomes in science at grade V of Harapan Baru Elementary School, Medan, in the 2024/2025 academic year. The research method used was an experimental method with a quantitative approach. To obtain the required data, a test instrument consisting of 30 questions was used. The sample size was 30 students using a purposive sampling technique. To determine students' initial abilities, the researcher conducted a pretest with an average score of 58.3. And the results of the posttest have increased from the pretest given previously with the average value of students reaching 83.86. It can be said that the level of success of student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation obtained r count ≥ r table with the results of 0.941 ≥ 0.361. Furthermore, hypothesis testing is comparing the value of t count ≥ t table with the results of 14.781 ≥ 2.042. With these results, Ha is accepted and Ho is rejected. Through the t-test it can be concluded that there is an influence of the contextual learning model on students' critical thinking abilities.